(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
From Volga to Ganga by Rahul Sankrityayan is a collection of twenty stories dealing with the contemporary social scenario. The book shows people’s avarice to power which doesn’t imply the only chair but it alludes towards many forms of power. Longing for power is not confine to the male rather it is the desire of human’s heart, bound not to particular sex, age, place, religion or caste. If a person grows ambitious or greedy for the power, he tries his best to achieve it either by hook or by crook. Although Volga to Ganga covers a huge range of people, periods and places yet this paper focuses on how a person understands the value of something when it starts to slip from his hands. Many times, its impact is so deep that it blinds the person to such an extent that he doesn’t want to see the consequences and its dark side. He only sees how much the grass is greener on another side. In the two stories of Volga to Ganga ’Nisha’ and ’Diva’, shifting of power and struggle to retain and gain is the main theme of these two stories. But the end of the story is not only very unexpected but thought-provoking. It makes one think about our limits for the ambition of position.